Electroanalytical methods in determination of selected biologically active compounds - Nawar, Amir Shaaban Farag Moham (Univerzita Pardubice, 2021)
This dissertation thesis describes possibilities and limitations for determination of biologically active substances in foodstuff and pharmaceutical dosage forms at various modified carbon-paste and glassy carbon electrodes using electrochemical techniques. It deals with voltammetric determination of ethylvanillin, methylvanillin as the total content, further with simultaneous determination of caffeine and vitamin B6 in commercially available energy drinks by differential pulse voltammetry. On the other hand, voltammetric determination of taurine was achieved after its derivatization to an electroactive product quantifiable in energy drinks. Finally, the antiarrhythmic drug Propafenone could be successfully determined in its tablet dosage form using adsorptive differential pulse voltammetry. Each analytical procedure proposed was optimized and obtained results found to be in good agreement with reference standard methods.
Elektroanalytické metody ke stanovení vybraných biologicky aktivních sloučenin
Keywords: voltametrie; vanillin; kofein; vitamín B6; taurine; Propafenon; energetické nápoje; farmaceutické preparáty (léčiva); Vanillin; energy drinks; caffeine; vitamin B6; taurine; propafenone; voltammetry; pharmaceutical analysis